Soil Management in the Breede River Valley Wine Grape Region, South Africa. 2. Soil Temperature - Fourie, J.C.; Freitag, K. (South African Journal of Enology and Viticulture, 2016)
Five soil management practices (treatments) were applied in a micro-sprinkler irrigated Chardonnay/99 Richter vineyard on a sandy clay loam soil near Robertson, commencing in April 1993 (one year after planting). The effect of the treatments on the soil temperature at a depth of 200 mm was measured on an hourly basis from April 1995 to March 1999. Differences in soil temperature between the un-mulched and mulched treatments, as measured in the grapevine rows, were negligible from late April to the end of August. From mid-September (grapevine bud break) to the end of March, the temperature of the mulched soil was, with the exception of the third week in October, lower than that of the un-mulched soil. Results indicated that soil temperatures during early spring had a slight effect on the onset of grapevine bud break. Mulching minimised the diurnal variation in soil temperature. The annual cover crop did not cause any delay in bud break and kept the soil temperatures below 25°C, with the exception of a three week period just before harvest.